A Search for Radio Technosignatures at the Solar Gravitational Lens Targeting Alpha Centauri - Tusay, Nick; Huston, Macy J.; Dedrick, Cayla M.; Kerby, Stephen; Palumbo III, Michael L.; Croft, Steve; Wright, Jason T.; Robertson, Paul; Sheikh, Sofia; Duffy, Laura; Foote, Gregory; Hyde, Andrew; et al. (The Astronomical journal, 2022)
Stars provide an enormous gain for interstellar communications at their gravitational focus, perhaps as part of an interstellar network. If the Sun is part of such a network, there should be probes at the gravitational foci of nearby stars. If there are probes within the solar system connected to such a network, we might detect them by intercepting transmissions from relays at these foci. Here, we demonstrate a search across a wide bandwidth for interstellar communication relays beyond the Sun’s innermost gravitational focus at 550 au using the Green Bank Telescope (GBT) and Breakthrough Listen (BL) backend. As a first target, we searched for a relay at the focus of the Alpha Centauri AB system while correcting for the parallax due to Earth’s orbit around the Sun. We searched for radio signals directed at the inner solar system from such a source in the L and S bands. Our analysis, utilizing the turboSETI software developed by BL, did not detect any signal indicative of a non-human-made artificial origin. Further analysis excluded false negatives and signals from the nearby target HD 13908. Assuming a conservative gain of 10 3 in the L band and roughly 4 times that in the S band, a ∼1 m directed transmitter would be detectable by our search above 7 W at 550 au or 23 W at 1000 au in the L band, and above 2 W at 550 au or 7 W at 1000 au in the S band. Finally, we discuss the application of this method to other frequencies and targets.